Chirality induction in platinum-containing polyaryleneethynylenes by exchange from achiral phosphine ligands to P-chiral phosphine ligands. (16th January 2023) - Aoki, Ryo; Horiuchi, Takashi; Makino, Soya; Sano, Natsuhiro; Imai, Yoshitane; Sogawa, Hiromitsu; Sanda, Fumio
Abstract: This study deals with chirality induction to the main chain of platinum (Pt)-containing aryleneethynylene polymers by ligand exchange reactions. The optically inactive polymers containing –(–CC–trans-Pt(PPh3 )2 –CC–)– moieties in the main chain undergo ligand exchange reactions with P -chiral diphosphines, ( R, R )-BenzP* and ( R, R )-QuinoxP* to give optically active polymers containing –(–CC–cis-Pt( P -chiral diphosphine)–CC–)– moieties. The ligand-exchanged polymers exhibit CD signals based on the conjugated main chain, indicating chirality induction to the main chain by the P -chiral ligands. The QuinoxP*-ligated polymers emit photoluminescence likely based on the transition from the QuinoxP* moieties. Quantum mechanical calculations predict reasonable CD, UV–vis absorption and photoluminescence spectra. Graphical abstract: Image 1 Highlights: Achiral Pt-containing polymers undergo ligand exchange with P -chiral diphosphines. The ligand-exchanged Pt-containing polymers exhibit CD signals. Chirality is induced to the Pt-containing polymers. Quantum mechanical calculations properly predict the optical properties.